The Influence of Learning Contents, Virtual Class Interaction, and Game-Based Learning Platform on Distance Learning Participants’ Satisfaction - Lidyana, Liza; Rahmawati, Ike Kusdyah; Handoko, Yunus; Wahyuni, Tri (Indonesian Journal of Instructional Media and Model, 2024)
PT PLN (Persero) as a State-Owned Enterprise (BUMN) has the responsibility to provide electricity to the people of Indonesia, including households, government agencies, and the industrial sector. To support employees’ competence and quality, PLN has an Education and Training Center (Pusdiklat PLN) which functions as a center for employees’ skill and career development. However, since the COVID-19 pandemic, Pusdiklat PLN has faced challenges in conducting face-to-face training and then switched to digital learning methods to ensure that training activities ran well. This study aims to analyze the effect of learning content, classroom interaction, and game-based learning platforms on the satisfaction of participants who take part in the digital learning program. This study uses a quantitative approach with PLN employees who took part in digital learning training in April 2024 as subjects. A total of 100 participants were selected using a purposive sampling technique. Data analysis was carried out using multiple linear regression with the assistance of SPSS 25 software. The results of the study showed that learning content, classroom interaction, and game-based learning platforms has a significant positive effect on participant satisfaction, both partially and simultaneously.